Analisis Property Damage di Area Tambang Pt. Pamapersada Nusantara Site Air Laya Provinsi Sumatera Selatan - Rycomatsu Rycomatsu; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. PT Pama Persada Nusantara is a company engaged in mining, in the process of coal mining, the company realizes that the frequency of risk of possible work accidents is very high. Events that occur unexpectedly in the process of mining activities, lack of employee awareness of PPE (Personal Protective Equipment) and the importance of signs in the mining area is one of the evaluation materials in occupational safety and health in minimizing mining accidents related to employees. For this reason, it is necessary to conduct research and studies on occupational safety and health to create safe conditions, avoid unsafe actions and supervision of every activity. Thus, the risk to each element involved in mining activities can be minimized especially in the Operations area . Based on the description above that is the basis for the author to conduct further research in the study with the title " Factor Analysis To Know the Causes of Accident Property Damage in the Operations Area of PT Pama Persada Nusantara   Site Air Laya South Sumatra Province".   Keywords: Occupational Safety and Health, Personal Protective Equipment, Property Damage, Mining, Accidents